Mesiodistal crown diameters of permanent dentition in schoolchildren from Lima - Pineda-Mejia, Martha (2014)
The purpose of this study was to determine the size of mesiodistal diameters of permanent teeth in a school population of the city of Lima, to analyze the differences between homologous teeth, sexual dimorphism of permanent teeth as well as the degree of variability of the measurements. Methodology: The study was conducted on 400 students of mestizos (200 men and 200 women) 10 to 12 years, from three schools in the districts of la Victoria and Barrios Altos, Lima city. The procedure was performed directly in the mouth using a Vernier caliper. Results and conclusions: it was found that 1M in the maxillary had the greatest mesiodistal diameter followed in descending order by 2M, IC, C, 1PM, 2PM, IL, in the mandible the 1M was higher followed in descending order by the 2M, 2PM, 1PM, C, IL, C. The mean difference between homologous teeth of the right and left side was very small in both genders, showing no statistical significance. The mesiodistal diameters of males were significantly higher than those of female, except in the case of the maxillary second premolar, the largest differences occurred in the first and second molar in the maxillary and the canine, first and second molars in the mandible. Teeth that showed greater variability in dimensions were the lateral incisors in the maxilla in both genders and the central incisors in males and second premolars in females in the mandible, which were identified as teeth with the greater potential to cause intra and inter arcades alterations. Averages found in the present study were higher than those found by other authors.